Breeding For Pre-harvest Sprouting (PHS) Tolerance in Greengram - Roja, V.; Harisatyanarayana, N.; Sateesh Babu, J.; Pranaya, J.; Mokshit Raja, V.; Pramod, P.; Sudhamani, K.; Jayalalitha, K. (Chronicle of Bioresource Management, 2024)
Pre-harvest sprouting (PHS) is the premature germination of seeds on the parent plant, while still in the field before harvest. This phenomenon is triggered by unfavorable weather conditions during the ripening period, leading to significant yield losses and reduced seed quality. The incidence of pre-harvest sprouting is very high in Vigna species especially in mungbean. High yielding varieties developed in recent years, despite of their high yield potential, could not increase the yields due to lack of tolerance to pre-harvest sprouting. The primary factors influencing tolerance to pre-harvest sprouting include fresh seed dormancy, hard seededness, pod wall thickness and pod wall epicuticular wax. Among these characters, fresh seed dormancy is found to be the most significant factor contributing to tolerance to pre-harvest sprouting. Hard seededness can increases tolerance to PHS by preventing seeds from germination. Therefore, it is crucial to develop the varieties that are tolerant to pre-harvest sprouting by comprehending the mechanisms and genetics underlying tolerance.